The importance of humanities in a career-focused educational environment - Zylstra, Geoff; Belli, Jill; Cabo, Candido; MacDonald, Sean; Michals, Robin; Sowder, Ann Marie; Swift, Christopher (Journal of Interdisciplinary Studies in Education, 2024)
This article addresses the role of the humanities in the context of professional degree programs that focus on technology, and shows how the humanities has enhanced career-oriented degree programs. As part of a larger college-wide initiative to develop interdisciplinary curricula, the National Endowment for the Humanities (NEH) awarded a grant to ***** College to both explore the relationship between the humanities and career-focused degree programs in STEM departments. This article describes the design and implementation of coursework that bridges the curricular gaps between humanities disciplines and technical or career-focused disciplines by bringing the humanities to bear on science and technology-oriented courses. If humanities appear as a body of knowledge, then they appear distinct from other disciplines. If humanities are viewed as conceptual frameworks that develop different modes of thinking, then the importance of the humanities to workforce development becomes clear.